Klothekan Music in the Brendung Ritual: An Ethnomusicological Analysis of Rain-Invoking Traditions in Pekalongan - Beny Permana; Dewi Puspita Ningsih; Muhammad Fajar Putranto; Gerry de Gerald (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2026)
The Brendung ritual represents a rain-invocation tradition that continues to be practiced by the community of Langensari Village, Kesesi District, Pekalongan Regency, Indonesia. This ritual incorporates klothekan music, performed using various household objects as musical instruments. This study aims to analyze the musical structure of klothekan within the Brendung ritual, to examine the relationship between musical structure and ritual processes, and to interpret its cultural significance within the community’s social life. A qualitative research design was employed using an ethnomusicological approach. Data were collected through participant observation, in-depth interviews with ritual specialists, musicians, and community leaders, as well as audiovisual documentation during ritual performances. The analysis focused on musical structure, including rhythmic patterns, inter-instrumental relationships, and emergent musical dynamics within klothekan performance. The findings indicate that klothekan music is constructed through simple yet interdependent rhythmic patterns performed collectively using an interlocking system among instruments such as boyong, bamboo slit drums (kentongan), buckets, cans, and metal trays. Repetitive rhythmic structures function to generate a ritual atmosphere that facilitates trance states and intensifies participants’ emotional engagement. Furthermore, klothekan music holds significant cultural meanings, functioning as a medium for ritual legitimization, social integration, spiritual communication, and the reinforcement of cultural identity. These findings demonstrate that klothekan music operates not merely as an accompaniment to ritual activities, but as a symbolic medium that sustains and amplifies collective ritual experience within the Brendung tradition.